2020
DOI: 10.1002/1878-0261.12825
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase OTUD6A promotes proliferation of cancer cells via regulating Drp1 stability and mitochondrial fission

Abstract: Dynamin-related protein 1 (Drp1) is a cytosolic protein responsible for mitochondrial fission and is essential in the initiation and development of several human diseases, including cancer. However, the regulation of Drp1, especially of its ubiquitination, remains unclear. In this study, we report that the ovarian tumor-associated protease deubiquitinase 6A (OTUD6A) deubiquitylates and stabilizes Drp1, thereby facilitating regulation of mitochondrial morphology and tumorigenesis. OTUD6A is upregulated in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…There is a relatively conserved loop, the Cys loop, which is responsible for the catalytic activation of OTUs. To investigate whether deubiquitinase activity is critical for OTUD6A functions in prostate cancer, we generated a catalytically inactive mutant of OTUD6A (OTUD6A C152A) 23 . We observed that reintroduction of wild-type (WT) but not the catalytically inactivated form of OTUD6A (C152A) reversed the reduced cell proliferation mediated by OTUD6A knockdown in PCa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a relatively conserved loop, the Cys loop, which is responsible for the catalytic activation of OTUs. To investigate whether deubiquitinase activity is critical for OTUD6A functions in prostate cancer, we generated a catalytically inactive mutant of OTUD6A (OTUD6A C152A) 23 . We observed that reintroduction of wild-type (WT) but not the catalytically inactivated form of OTUD6A (C152A) reversed the reduced cell proliferation mediated by OTUD6A knockdown in PCa cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OTUD3 facilitates PTEN-related tumor suppressive responses and inhibits breast tumorigenesis, while in lung cancer, OTUD3 promotes tumorigenic phenotypes by stabilizing GRP78 53 , 54 . OTUD6A was reported to deubiquitinate and stabilize Drp1 and to regulate mitochondrial morphology in colon cancer 23 . In our study, we found that many OTU family members exhibited DNA amplification in PCa, while OTUD6A showed a specific and high amplification rate (15–20%), which emphasizes the potential roles of OTUD6A in the regulation of PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a limited number of studies on OTUD6A. However, it has been demonstrated that OTUD6A enhances the protein levels of one of the crucial EMT inducers, Snail [ 22 ], and promotes colorectal cancer by deubiquitinating and stabilizing DRP1 [ 23 ]. Therefore, the present study and the previous reports suggest that OTUD6A could be a feasible therapeutic target in human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The tumorigenic roles of OTUD6A have been demonstrated previously. OTUD6A enhances the protein levels of Snail, an EMT (epithelial-mesenchymal transition) inducer [ 22 ], and promotes tumorigenecity by deubiquitinating and stabilizing Drp1 [ 23 ]. We found that OTUD6A deubiquitinates Aurora-A to stabilize and activate by interacting through the kinase domain of Aurora-A.…”
Section: Introductionmentioning
confidence: 99%